IMPLEMENTASI MOBILE COMMERCE SEBAGAI STRATEGI MARKETING PARFUM MULTAZAM PRINGSEWU - Juhainah, Juhainah (STMIK Pringsewu, 2024)
Perfume Multazam is one of the stores that sell perfume and Multazamt. It is no longer a secret that women can not be separated from these two things because the two things are primarily women. system that runs is still not effective in terms of marketing, in the era of modern customers want every thing to buy with ease or speed information to facilitate all activities. The purpose of the research is to make e-commerce mobile app sales Multazam Perfume. In building this system the author uses a prototype method where data collection techniques are conducted through interviews and a literature review. While assisting analys is and system design nursing PHP and MySQL DataBase. The results of research on Multazam Perfume can be concluded with the creation of mobile e-commerce applications Parfume Multazam sales can facilitate customers to make reservation transactions.